Who makes on-the-run Treasuries special? - Graveline, Jeremy J.; McBrady, Matthew R. (Journal of Financial Intermediation, 2011)
The most recently issued, on-the-run, Treasuries are extremely liquid and frequently trade at a premium in both the cash and repo, or financing, markets. Previous research suggests that both the cash and repo premiums reflect demand from buy-and-hold investors who value the superior liquidity of these securities and are reluctant to lend them in the repo market. We find evidence that premiums in the repo market are also closely related to market participants’ demand to hedge interest rate risk associated with their holdings of fixed income securities.